2023
DOI: 10.3389/fpubh.2023.1228632
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and health behavior in children and adolescents: a systematic literature review

Nirmal Gautam,
Getenet Dessie,
Mohammad Mafizur Rahman
et al.

Abstract: Socioeconomic status affects individuals’ health behaviors and contributes to a complex relationship between health and development. Due to this complexity, the relationship between SES and health behaviors is not yet fully understood. This literature review, therefore, aims to assess the association between socioeconomic status and health behaviors in childhood and adolescence. Preferred Reporting for Systematic Review and Meta-Analysis protocol guidelines were used to conduct a systematic literature review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 147 publications
(268 reference statements)
0
3
0
Order By: Relevance
“…Additionally, there seems to be an association between parents' educational level and child overweight/obesity, with the lowest educational level corresponding to the highest prevalence of obese children [30]. Furthermore, in relation to socioeconomic status and diet, Gautam and colleagues [33] found that higher socioeconomic status was associated with higher consumption of breakfast, fruit, vegetables, dairy products, and a balanced diet in general. This aligns with our findings, confirming that the adoption of a Mediterranean diet among families with higher education levels promotes a healthy weight status for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there seems to be an association between parents' educational level and child overweight/obesity, with the lowest educational level corresponding to the highest prevalence of obese children [30]. Furthermore, in relation to socioeconomic status and diet, Gautam and colleagues [33] found that higher socioeconomic status was associated with higher consumption of breakfast, fruit, vegetables, dairy products, and a balanced diet in general. This aligns with our findings, confirming that the adoption of a Mediterranean diet among families with higher education levels promotes a healthy weight status for their children.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Our findings with adolescents are consistent with previous studies. 46 , 48 - 50 Fortunately, adolescents generally have a lower dependence on nicotine because of shorter exposure histories, which makes them more likely to quit. 51 Therefore, efforts should be made to reach families with low SES and uneducated fathers to raise awareness and encourage adolescents to never smoke or quit before they get addicted.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sociodemographic background on the psychological characteristics of children grappling with chronic illnesses is a multifaceted domain warranting comprehensive examination. Socioeconomic status significantly influences access to healthcare resources, shaping the child's psychological resilience and coping strategies 22 . Economic disparities may contribute to heightened stress, impacting mental well-being 23 .…”
Section: The Role Of Sociodemographic Background Variables In the Dev...mentioning
confidence: 99%